Sex disparities in the association between acute myocardial infarction and colon cancer risk - Shing‐Hsien Chou; Chia‐Pin Lin; Yu‐Sheng Lin; Ting‐Hein Lee; Chan‐Keng Yang; Yu‐Sheng Lin; Pao‐Hsien Chu (Cancer Medicine, 2023)
Abstract Background Acute myocardial infarction (AMI) and colon cancer share similar risk factors. Studies have suggested an association between AMI and colon cancer; however, evidence is conflicting. Whether sex disparities exist in this association in the real world remains unknown. Methods In this population‐based retrospective cohort study, 94,780 and 97,987 male patients and 38,697 and 72,007 female patients with and without new‐onset AMI, respectively, from January 1, 2001, to December 31, 2012, were enrolled from Taiwan's National Health Insurance Research Database. Inverse probability of treatment weighting (IPTW) was used to balance covariates across study groups. The primary outcome was a new diagnosis of colon cancer. Results The incidence rate of colon cancer was 1.54 (95% confidence interval [CI] = 1.46–1.62) and 1.40 (95% CI = 1.32–1.48) per 1000 person‐years in the male patients and 1.62 (95% CI = 1.50–1.74) and 1.22 (95% CI = 1.13–1.32) in the female patients, in the AMI and non‐AMI groups, respectively. AMI was associated with a significantly higher risk of colon cancer in the female patients (hazard ratio [HR] = 1.31, 95% CI = 1.06–1.61) but not in the male patients (HR = 1.09, 95% CI = 0.95–1.26). In the subgroup analysis, the association between AMI and colon cancer in the female patients was stronger in those aged ≥65 years (HR = 1.28, 95% CI = 1.13–1.44). Conclusions An increased risk of colon cancer was observed only in the female patients with AMI. The association between AMI and colon cancer in the female patients was the most evident in those aged ≥65 years.